Study on Method for Chemical Reaction Activation Energy Acquiring of Dry Insulation Equipment Based on TGA. Issue 2 (March 2020) - Zhang, Xin; Zhang, Xinjie; Ma, Hao; Wang, En; Wang, Wei; Ma, Xiaoguang; Dun, Chao
Abstract: Thermogravimetric analysis is an important method in chemical reaction kinetic analysis. This paper introduces thermogravimetric analysis into the field of insulation performance analysis of dry insulation equipment, and introduces the thermogravimetric analysis experimental methods of epoxy resin materials. On this basis, the calculation principle of the activation energy of the chemical reaction is analysed, and two calculation methods for the activation energy of dry insulation equipment are proposed.